INVESTIGATING THE DIFFICULTIES ON STUDENTS’ WRITING OF RECOUNT TEXT - Riska Amanda; Ridha Ilma; Deta Desvitasari (PROJECT (Professional Journal of English Education), 2024)
Writing is one of the important skills in learning English, writing can provide useful information for other people who need it. This study aimed to investigate the difficulties faced by eighth grade students in one of State Junior High school in Palembang in writing recount texts. It outlines the qualitative research approach, specifically a case study design, used to explore the difficulties faced by eighth farde students in writing recount texts. Homogenous sampling method was employed to select participants from the eighth grade class, four students were selected as participants who have difficulties in writing recount texts. Data collection involved interviews. Thematic analysis technique was used in analyzing the data. The result of this study showed that students encountered difficulties when writing recount texts such as lack of understanding of recount texts generic structure, lack of grammar mastery, lack of vocabulary, lack of undestanding mechanics use. Improvement from teachers and proactive efforts of students will help contribute to enhanced writing skills and solve students’ difficulties in writing recount texts.